Chechnya's status within the Russian Federation : Ramzan Kadyrov's private state and Vladimir Putin's federal "Power Vertical" - Halbach, Uwe (2018)
Zusammenfassung: In the run-up to the Russian presidential elections on 18 March 2018, the Kremlin further tightened the federal “vertical of power” that Vladimir Putin has developed since 2000. In the North Caucasus, this above all concerns the republic of Dagestan. Moscow intervened with a powerful purge, replacing the entire political leadership. The situation in Chechnya, which has been ruled by Ramzan Kadyrov since 2007, is conspicuously different. From the early 2000s onwards, President Putin conducted a policy of “Chechenisation” there, delegating the fight against the armed revolt to local security forces. Under Putin’s protection, the republic gained a leadership which is now publicly referred to by Russians as the “Chechen Khanate”, among other similar expressions. Kadyrov’s breadth of power encompasses an independent foreign policy, which is primarily orientated towards the Middle East. Kadyrov emphatically professes that his republic is part of Russia and presents himself as “Putin’s foot soldier”. Yet he has also transformed the federal subject of Chechnya into a private state. The ambiguous relationship between this republic and the central power fundamentally rests on the loyalty pact between Putin and Kadyrov. However, criticism of this arrangement can now occasionally be heard even in the Russian president’s inner circles. With regard to Putin’s fourth term, the question arises just how long the pact will last. The price that Moscow was willing to accept for Chechnya’s “pacification” by Kadyrov and his supporters includes serious human-rights violations. Since 2017 these have increasingly moved back into the focus of international politics and reporting